Implementasi Metode Simple Addtive Weighting Pada Sistim Manajemen Layanan Alisha Laundry Berbasis Web - Ramadhan, Rizky; Hidayat, Alfin; Farisqi Panduardi (Jurnal Informatika dan Komputer, 2025)
Alisha Laundry is a laundry service provider. Since its founding, Alisha Laundry has been committed to providing the best service with a focus on quality, efficiency and customer satisfaction. Conventional assessment and management of laundry services is usually carried out through direct observation and manual assessment based on certain criteria. This method often has disadvantages such as high subjectivity, lack of standardization, and low time efficiency. This research examines the application of the Simple Additive Weighting (SAW) method in the web-based Alisha Laundry service management system to increase efficiency and effectiveness in decision making. SAW is used to assess and select the best alternative based on several main criteria: service quality, price, and turnaround time. This process involves normalizing the criteria values, assigning weights according to the level of importance of each criterion, and calculating the total score for each alternative. Implementing SAW allows Alisha Laundry to manage resources better and improve the performance assessment process, thereby providing more objective and targeted decisions.